Material Composition Testing Related to Measurement Instrument Enclosure Design and Safety - Gaber Beges; Domen Hudoklin (Applied Sciences)
The polymeric insulating materials widely used in measuring instrument enclosures must meet specific flammability requirements. In this study, we systematically assessed the impact of minor compositional changes, such as pigments and fillers, on horizontal burning (HB) classification according to the EN 60695-11-10 standard. We tested 64 polymer combinations at thicknesses of 1.5 mm and 3.0 mm, classifying samples into HB, HB40 or HB75 categories. The results demonstrated that additives significantly influenced the HB classifications more than thickness. Specifically, we classified 31 samples as HB, 16 as HB40, 15 as HB75, while two were unclassifiable. Several material groups consistently achieved specific HB classifications regardless of minor additive variations. These findings offer manufacturers clear guidance for selecting polymer-additive systems, facilitating informed decisions and enabling a streamlined “worst-case” testing strategy. Ultimately, this approach enhances manufacturers’ ability to efficiently achieve product safety compliance, reducing certification costs without compromising safety.